Experiences in the training of tourism entrepreneurs:: towards a strengthening of entrepreneurial capacities. The case of the Jáchal Department, San Juan, Argentina - Santandreu, María Marcela; Narvaez, Estela; Marsilgia, Javier (Cooperativismo & Desarrollo, 2022)
This paper shows the results of the training actions developed within the framework of the extension project called "Promotion and strengthening of the entrepreneurial capacities of tourist entrepreneurs of the Jáchal-San Juan department" are exposed, which arises because of demands established by entrepreneurs within the framework of research and extension projects previously carried out in the area.The Department of Jáchal has a great diversity of resources that make it possible to carry out various productive and touristic activities and offer significant development potential. Therefore, through this training activity, it was sought to accompany the recipients in the process of searching for and building a strategy to strengthen touristic activities in their locality, based on a shared vision and the identification of opportunities. of enterprises that make it possible to value their local identity, while taking advantage of the benefits of tourism, within a framework of economic, social, and environmental sustainability. Given this, it was sought to promote the generation of sustainable business ideas that allow the recipients their integration into the productive activity and thus contribute to increasing their income and avoiding their migration to other locations, considering the tourist potential of the territory itself.The work is presented as an initial training proposal for entrepreneurs, which has traveled a path of construction and collective reflection and has results derived from the implementation that, a priori, allow us to visualize its critical points and strengths. A participatory methodology was used both for the development of the meetings and workshops and for the definition of the contents of the process, with special emphasis on awareness of the potential of the communities to build and consolidate touristic proposals with a strong local identity, while strengthening the entrepreneurial skills of the recipients involved.
Keywords: entrepreneurship; training; territorial development; tourism; business strengthening